2020
DOI: 10.4149/neo_2019_190110n29
|View full text |Cite
|
Sign up to set email alerts
|

miR-17-5p knockdown inhibits proliferation, autophagy and promotes apoptosis in thyroid cancer via targeting PTEN

et al.

Abstract: Thyroid cancer is one common endocrine malignancy with various pathological types. MicroRNAs (miRNAs) play essential roles in development, prognosis and treatment of thyroid cancer. However, the role of miR-17-5p in thyroid cancer progression and its mechanism remain poorly understood. The expressions of miR-17-5p and phosphatase and tensin homolog (PTEN) were measured in thyroid cancer tissues and cells by quantitative real-time polymerase chain reaction or western blot. Cell proliferation and apoptosis were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…PTEN, which was identified in 1977, is a classical cancer suppressor and possesses lipid and protein phosphatase activities [28]. In malignant cells, PTEN has been shown to be silenced by the expressions of a number of micro-RNAs and able to drive a transcriptional program that is essential for maintaining the malignant state of diseases, such as cell proliferation, apoptosis, invasion, and adhesion [29,30]. Shi et al reported that PTEN was targeted by miR-17-5p to regulate the proliferation and autophagy of thyroid cancer [30]; Chen et al proved that miR-21 regulated the proliferation and apoptosis of bladder cancer mediated through PTEN [31]; PTEN was also targeted by miR-216a to enhance the proliferation and fibrogenesis of human cardiac fibroblasts [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PTEN, which was identified in 1977, is a classical cancer suppressor and possesses lipid and protein phosphatase activities [28]. In malignant cells, PTEN has been shown to be silenced by the expressions of a number of micro-RNAs and able to drive a transcriptional program that is essential for maintaining the malignant state of diseases, such as cell proliferation, apoptosis, invasion, and adhesion [29,30]. Shi et al reported that PTEN was targeted by miR-17-5p to regulate the proliferation and autophagy of thyroid cancer [30]; Chen et al proved that miR-21 regulated the proliferation and apoptosis of bladder cancer mediated through PTEN [31]; PTEN was also targeted by miR-216a to enhance the proliferation and fibrogenesis of human cardiac fibroblasts [32].…”
Section: Discussionmentioning
confidence: 99%
“…In malignant cells, PTEN has been shown to be silenced by the expressions of a number of micro-RNAs and able to drive a transcriptional program that is essential for maintaining the malignant state of diseases, such as cell proliferation, apoptosis, invasion, and adhesion [29,30]. Shi et al reported that PTEN was targeted by miR-17-5p to regulate the proliferation and autophagy of thyroid cancer [30]; Chen et al proved that miR-21 regulated the proliferation and apoptosis of bladder cancer mediated through PTEN [31]; PTEN was also targeted by miR-216a to enhance the proliferation and fibrogenesis of human cardiac fibroblasts [32]. Similarly, in the present study, we found that PTEN not only inhibited the migration and invasion, and induced apoptosis of EC cells, but also reversed the effect of miR-25-3p on EC cells, which further confirmed that miR-25-3p regulated the migration, invasion, and apoptosis of EC cells by targeting PTEN.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, previous studies reported that miR‐17‐5p regulates autophagy in several diseases. 33 , 34 Bobbili et al 35 described miR‐17‐5p as an essential regulator of autophagy and an ‘alarm signal’ in cancer. We observed a negative association between miR‐17‐5p and autophagy, as si‐HOTAIR suppressed autophagosome formation in LPS‐stimulated A549 and BEAS‐2B cells, whereas miR‐17‐5p inhibition upregulated ATG2, ATG7, and ATG16 protein expression.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, numerous studies have shed light on the relationship between miRNAs and PTEN. Apoptosis, autophagy, and proliferation of cancer cells are affected by miRNAs in different cancers [102,103]. As miRNAs are well-known regulators in cancer cells, understanding their impact on PTEN expression can be beneficial in providing novel therapeutics.…”
Section: Role In Cancermentioning
confidence: 99%